Impacts of dairy cooperatives in smallholder dairy production systems: a case study in Assam - Baban Bayan (Agricultural Economics Research Review, 2023)
This paper assesses the impact of membership of dairy cooperative societies (DCS) on the performance of smallholder dairy production systems in Assam using matching techniques. Findings show that membership of DCS contributes towards improving yields of dairy animals, farm income and employment; and also, to household milk consumption. Nonetheless, it does not have a significant impact on technology adoption. The milk prices offered by dairy cooperatives are also less compared to the prices in wet market. These results indicate towards the need to improve dairy farmers linkages through cooperatives or other such instituions.